The problems of mathematics education at secondary schools and gymnasia - Apynis, Antanas; Mazėtis, Edmundas (Lietuvos matematikos rinkinys, 2011)
The article reviews the ties between secondary schools/gymnasia and universities, and also discusses complementary mathematics education. Major attention is directed to the general mathematics curricula of general education and secondary education. A proposal of developing an integral mathematics education curriculum for gymnasium as well as withdrawing the state school graduation curriculum (by organising the examination under the general mathematics education curriculum) has been put forward.